A contribution to resource-efficient construction: Design flow and experimental investigation of structurally optimised concrete girders. (15th April 2023) - Pressmair, Nadine; Kromoser, Benjamin
Abstract: In view of the current global climate challenges, the urgency for reduction of material consumption in the construction sector becomes clear. In this context, the present study concentrates on enhancing resource efficiency in concrete construction via the use of structural optimisation software tools as a guide for finding the geometry of optimised, mass-reduced concrete girders. Within a test series of eight specimens, varying parameters regarding the consulted optimisation strategy, the stirrup reinforcement type and concrete coverage were assessed. The experimental investigation was followed by a profound structural analysis, identifying peculiarities in the load-bearing behaviour and stiffness as well as two main failure modes characteristic of the optimised girder geometries. The comparison with full concrete girders illustrates the achieved reduction in concrete mass, the decrease of the Global Warming Potential of the production phase as well as the increase in the overall performance. Highlights: Design of resource-efficient concrete girders assisted by structural optimisation. Profound analysis of the experiments, with a detailed crack formation history. Two main failure modes identified for the tested optimised girders. Less environmental impact of optimised girders than of full pendants.